2005
DOI: 10.1210/en.2004-0565
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Secretion of Angiotensin II by the Prostate Gland in Vitro

Abstract: The renin angiotensin system has been shown to have tissuerelated functions that are distinct from its systemic roles. We showed that angiotensin II type 1 (AT 1 ) receptors are present in mammalian sperm, and angiotensin II stimulates sperm motility and capacitation. In addition, angiotensin II is present in human seminal plasma at concentrations higher than found in blood. In testing the possibility that the prostate may be the source of seminal plasma angiotensin II, mRNA coding for angiotensinogen, (pro)re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…More surprisingly, there is considerable evidence that the male reproductive organs contain reninangiotensin system components, such as angiotensinogen, renin, angiotensin I -converting enzyme, and AT 1 and AT 2 receptors. O'Mahony et al suggested that the prostate gland may be the source of angiotensin II found in seminal fluid and that angiotensin II production may be regulated by androgen (39,40). Based on this accumulated evidence and our results, the prostate itself seems to be a target for angiotensin, and the prostatic renin-angiotensin system may affect the development of prostate cancer.…”
Section: Discussionsupporting
confidence: 73%
“…More surprisingly, there is considerable evidence that the male reproductive organs contain reninangiotensin system components, such as angiotensinogen, renin, angiotensin I -converting enzyme, and AT 1 and AT 2 receptors. O'Mahony et al suggested that the prostate gland may be the source of angiotensin II found in seminal fluid and that angiotensin II production may be regulated by androgen (39,40). Based on this accumulated evidence and our results, the prostate itself seems to be a target for angiotensin, and the prostatic renin-angiotensin system may affect the development of prostate cancer.…”
Section: Discussionsupporting
confidence: 73%
“…Intriguingly, a 3-fold to 5-fold higher concentration of angiotensin II was confirmed in seminal fluid in comparison with that in blood (32), which strongly supports the existence of RAS in the prostate gland. Likewise, it was reported that there was a high concentration of angiotensin II in pancreatic cancer tissue compared with that in normal tissue (33), and RAS components, including angiotensinogen, angiotensin II receptor type 1, and renin, have been identified in the islets of Langerhans (34).…”
Section: Discussionsupporting
confidence: 58%
“…It has been suggested that ACE2 may oppose the effects of ACE on the organ and tissue levels through the generation of Ang-(1-7) by the local RAS [15]. The local RAS systems have been detected in various species and in diverse organs, such as the brain, the testes, the prostate, the pancreas, the adrenal gland, and the mammary glands [16][17][18][19][20][21][22]. The local RAS systems enable the generation of Ang II, and may therefore exert biological activity on an organ level.…”
Section: Introductionmentioning
confidence: 99%